ATTEMPTION OF BRAND PROTECTION FROM THE EQUALITY OF BRAND INFRINGEMENT: A Case Study of Indonesian Supreme Court Decision No. 332K/Pdt.Sus-HKI/2021 - Hamid, Adnan; Dwi Sasongko, Baried; Rini, Dian Puspito (jfpublisher, 2022)
The dispute over the brand infringement from the use of word 'Strong' by PT Unilever Indonesia, Tbk on their oral care product, 'Pepsodent Strong 12 Jam' has the same name as 'Strong' on the product belonging to Hardwood Private Limited (holding company of the Orang Tua Group). Indonesian Supreme Court Decision on March 30, 2021 No. 332K/Pdt.Sus-HKI/2021, they do not provide legal protection for the first registrant of strong mark and legal certainty for registered brand owners and this is contrary to the passive judges principle in the KUHAP (Criminal Procedure Code). The word of 'Strong' has a distinguishing power with the brand 'Pepsodent Strong 12 Jam'. The brand naming 'Strong' is formed from a descriptive word which is a common word in a foreign language which has a certain meaning and the owner of the registered brand cannot monopolize it. The TRIPS (Trade-Related Aspects of Intellectual Property Rights) agreement provides exceptions for brand protection based on fair use principles contained in brand dispute jurisprudence involving common words. This research method is normative research through a legal approach. The comprehension and regulation will be reviewed on Law No. 20/2016 concerning of Marks and Geographical Indications and HIR (Herzien Inlandsch Reglement). The word 'Strong' is an adverb, which means 'in a strong or forceful manner' which is quoted from Merriem Webster. Therefore, using its word is public property and it can be used by everyone,but not for personal used.